Effect of prebiotic, synbiotic and phytobiotic supplements on performance, digestibility and blood parameters of lambs - Saravani, M; Hajipour, M; Khorshidi, KJ; Mousavi Kashani, SM; Shoorang, P (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to investigate the effect of adding dietary prebiotic, synbiotic, and phytobiotic supplements on growth performance, carcass traits, apparent digestibility of nutrients, and some blood parameters of Zell fattening lambs.For this purpose, 24 male Zell lambs with an average age of 5 months and a weighted mean of 25.4±0.50 were used for 90 days. The experimental treatments included 1) a control group (without supplement), 2) treatment containing 2gr prebiotic supplement (A-MAX), 3) treatment containing 3gr synbiotic supplement (Biomin IMBO), and 4) treatment containing 6gr phytobiotic supplement (Bioherbal) given to each head of lamb per day. The results of growth performance traits indicated a significant difference between experimental treatments in final fattening weight, dry matter intake, daily weight gain, and feed conversion ratio (p<0.05). According to the results of the apparent digestibility of nutrients, a significant difference existed between experimental treatments in terms of apparent digestibility of dry matter, crude protein, the NDF, and ADF (p<0.05). The results of some blood serum parameters indicated a significant difference between experimental treatments in terms of glucose, cholesterol, triglyceride, and blood urea nitrogen concentration (p<0.05). According to the result of quantitative characteristics of the carcass, a significant difference existed between trial treatments in terms of the hot carcass weight, hot carcass percent, cold carcass weight, cold carcass percent, thigh percent, and shoulder percent (p<0.05). The results of this study showed that adding a 4gr dietary synbiotic supplement could improve growth performance indicators, valuable carcass parts, and apparent digestibility of nutrients in Zell fattening lambs.